Daytime Fluctuations in Blood of Tissue-Type Plasminogen Activator (t-PA) and Its Fast-Acting Inhibitor (PAI-1) - Kluft, C; Jie, A F H; Rijken, D C; Verheijen, J H (Thrombosis and Haemostasis, 1988)
Circadian fluctuation in blood fibrinolytic activity was studiedin 10 volunteers in the day-time period at 09.00, 12.00 and15.0 h. Activity of tissue-type plasminogen activator (t-PA) wasfound to increase from 09.00 to 15.00 h in accordance with knownresults with global assays of blood activity.
Keywords: Fibrinolysis; Tissue-type plasminogen activator; Plasminogen; activator inhibitors; Circadian rhythm